Composite diaphragm, preparation method of composite diaphragm, battery containing composite diaphragm and manufacturing method of battery

By using an oil-based coating composed of porous inorganic filler and modified adhesive material on the lithium-ion battery separator, the problem of shrinkage or cracking of the separator at high temperature is solved, and the battery is high safety and good electrochemical performance are achieved.

CN119833879AActive Publication Date: 2025-04-15SVOLT ENERGY TECHNOLOGY CO LTD

Patent Information

Application Number
CN202510062893.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-15
Publication Date
2025-04-15
Estimated Expiration
2045-01-15

AI Technical Summary

Technical Problem

Existing lithium-ion battery separators are prone to shrink or break in high temperature environments, resulting in the risk of thermal runaway, combustion and explosion, and existing improvement measures cannot completely eliminate safety hazards.

Method used

A composite separator is used, which includes a base film and an oily coating provided on the surface of one side of the base film. The oily coating consists of a porous inorganic filler, a polymer material and an adhesive material. By adjusting the pore size of the porous inorganic filler and the modification of the adhesive material, the peel strength between the oily coating and the base film is controlled, so that it is transferred to the surface of the positive electrode sheet in the hot pressing process to form a high heat-resistant film.

Benefits of technology

It effectively avoids the problem of separator shrinkage and rupture caused by base film changes in high temperature environments, improves the safety of the battery, and does not affect the electrochemical performance of the positive electrode sheet.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005243428200000191
    Figure BDA0005243428200000191
  • Figure BDA0005243428200000201
    Figure BDA0005243428200000201
  • Figure BDA0005243428200000202
    Figure BDA0005243428200000202
Patent Text Reader

Abstract

The invention belongs to the technical field of battery materials, and provides a composite diaphragm, a preparation method thereof, a battery containing the composite diaphragm and a manufacturing method, the composite diaphragm comprises a base diaphragm and an oily coating arranged on one side surface of the base diaphragm; the oily coating comprises a porous inorganic filler, a polymer material and a bonding material; and the peel strength F1 between the oily coating and the base film and the pore diameter L of the porous inorganic filler meet the relationship of 170 * 10 <-9 > N < = L * F1 < = 230 * 10 <-9 > N. Through association of F1 and L, the oily coating can obtain a special effect of strong bonding force but low peeling strength with a base film, so that the oily coating is fully transferred to the surface of a positive pole piece through a hot pressing process in the assembling and manufacturing process of the battery, which is equivalent to that a layer of high-heat-resistant film is transferred to the surface of the positive pole piece; and under the condition that the electrochemical performance of the positive pole piece is not influenced, the effect of isolating the positive pole from the negative pole is achieved at high temperature.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of battery materials and relates to a composite diaphragm, a preparation method thereof, a battery containing the composite diaphragm and a manufacturing method thereof. Background Art

[0002] The rapid development and widespread application of lithium-ion battery technology have made it an indispensable part of modern life. From electric vehicles to large energy storage power stations to 3C electronic products, lithium batteries have occupied an important position in many fields due to their excellent performance. However, as battery cells continue to develop towards larger capacity and higher rates, concerns and concerns about battery thermal runaway, combustion and explosion are also increasing, which undoubtedly puts more stringent requirements on battery safety.

[0003] As a key component inside lithium-ion batteries, the separator plays a vital role. It not only needs to effectively isolate the positive and negative electrodes at room temperature to prevent short circuits, but also needs to remain stable at high temperatures to avoid thermal runaway caused by temperature increases. Therefore, the development of separators with high safety characteristics has become an important research direction to improve the overall performance and safety of lithium-ion batteries.

[0004] In order to achieve the above goals, the researchers proposed a solution to optimize and improve the diaphragm by coating heat-resistant materials, such as aramid, polyimide, etc., to form a heat-resistant coating. These heat-resistant materials are generally formed by dissolving an oily slurry obtained by using an organic solvent, and in order to ensure the adhesion of the heat-resistant layer and the hardness of the battery core, it is necessary to further coat it with an aqueous slurry containing a glue material. This method of preparing the oily coating and the aqueous coating separately often involves multiple winding and unwinding of the diaphragm, which is a cumbersome process and is not conducive to the control of processing costs.

[0005] To this end, CN106058126A discloses a functional coating diaphragm and a battery containing the diaphragm, the coating diaphragm: composed of a polyolefin substrate and a coating applied to the surface of the polyolefin substrate; the coating preparation slurry includes aqueous polyvinylidene fluoride, inorganic nano-ceramic particles and hydroxymethyl cellulose glue. This prior art uses aqueous polyvinylidene fluoride binder combined with inorganic nano-ceramic particles with high heat resistance to prepare a functional coating diaphragm, so that the resulting diaphragm not only has the performance of a conventional oil-based P (VDF-HFP) coated diaphragm, but also has better bonding performance and heat resistance, which can effectively inhibit the shrinkage of the diaphragm at high temperature and the shedding of the coating. However, for the solution of directly forming a coating on the base film, although the composition and materials of the coating are optimized to utilize its further improved heat resistance or bonding properties, the base film itself often does not have sufficient heat resistance. When facing more extreme and harsh environments such as extremely high temperatures, it will still cause the overall diaphragm to shrink or rupture, thereby causing contact between the positive and negative electrodes, resulting in the risk of thermal runaway of the battery.

[0006] In view of this situation, another solution is to directly coat a layer of heat-resistant ceramic material on the surface of the positive electrode. For example, CN112397716A discloses an oily ceramic slurry, a preparation method thereof, a positive electrode sheet coated with the slurry, and a lithium-ion battery. The prior art solves the problems of large swelling and easy falling off of the water-based ceramic coating, and easy phase separation, easy falling off, and hardness of the oily ceramic coating by using a first binder, a second binder, a ceramic powder, and an organic solvent. By using the oily ceramic slurry of the invention to prepare an edge-coated positive electrode sheet, the problem of positive and negative short circuit can be solved. However, although the ceramic layer formed by directly coating the positive electrode sheet can continue to play an isolating role when the diaphragm shrinks and ruptures, this method has the disadvantage of seriously sacrificing the energy density of the battery and increasing the manufacturing cost.

[0007] In view of the above, the existing improvement measures cannot completely eliminate all potential safety hazards. Therefore, the research and development of high-safety diaphragms still needs to be continued in depth to ensure that the safety protection performance of lithium-ion batteries is further guaranteed, while balancing the relationship between battery performance such as energy density and cost-effectiveness, and providing the market with more complete product options. Summary of the invention

[0008] In view of the problems existing in the prior art, the object of the present invention is to provide a composite diaphragm, a preparation method thereof, a battery containing the same and a manufacturing method, wherein the composite diaphragm comprises a base film and an oily coating disposed on one side surface of the base film; the oily coating comprises a porous inorganic filler, a polymer material and an adhesive material; the peel strength F between the oily coating and the base film is 1 The relationship between the pore size L of the porous inorganic filler and the-9 N≤L×F 1 ≤230×10 -9 N. by F. 1 The association with L enables the oily coating to obtain the special effect of strong adhesion but low peeling strength with the base film, so that the oily coating can be fully transferred to the surface of the positive electrode through the hot pressing process during the assembly and manufacturing process of the battery, which is equivalent to transferring a layer of high heat-resistant film on the surface of the positive electrode, so that it can isolate the positive and negative electrodes at high temperature without affecting the electrochemical properties of the positive electrode.

[0009] To achieve this object, the present invention adopts the following technical solutions:

[0010] In a first aspect, the present invention provides a composite diaphragm, comprising a base film and an oily coating disposed on one side surface of the base film; the oily coating comprises a porous inorganic filler, a polymer material and an adhesive material; the pore size (diameter) of the porous inorganic filler is denoted as L, and the peel strength between the oily coating and the base film is denoted as F 1 , then 170×10 -9 N≤L×F 1 ≤230×10 -9 N.

[0011] The oily coating described in the present invention includes a porous inorganic filler. Porous means that there are pore structures on the surface and inside of the inorganic filler. The porous inorganic filler structure reduces the contact area between the oily coating and the base film, thereby reducing the peeling strength between the oily coating and the base film. Therefore, when the composite diaphragm described in the present invention is used to prepare a battery, for example, in the hot pressing process of preparing a square shell battery, the oily coating can be transferred from the base film to the surface of the positive electrode plate, which is equivalent to providing a layer of high heat-resistant film on the surface of the positive electrode plate, retaining the characteristics of this working mode, avoiding the isolation failure caused by the shrinkage and rupture of the overall diaphragm due to changes in the base film under extreme working conditions such as high temperature, further effectively avoiding the occurrence of thermal runaway, combustion and explosion problems, and greatly improving the safety of the battery.

[0012] It should be noted that, in the oily coating, the larger the pore size of the porous inorganic filler, the smaller the contact area between the porous inorganic filler and the base film, and the smaller the peel strength (adhesion). 1 ≤170×10 -9 N causes the pore size to be too small, and the effect of the inorganic filler and the polymer material forming a uniform mixed phase becomes worse; 1 ≥230×10 -9When the pore size is too large, the inorganic filler will float in the oily slurry, and the heat resistance and coating transfer effect of the oily coating will deteriorate. It should also be noted that the pore size L in the porous inorganic filler is in nm, while the peel strength F 1 The unit is N / m. 1 Unit conversion is required so that L×F 1 The unit of the calculation result is N.

[0013] The following are preferred technical solutions of the present invention, but are not intended to be limitations of the technical solutions provided by the present invention. Through the following technical solutions, the technical objectives and beneficial effects of the present invention can be better achieved and realized.

[0014] As a preferred technical solution of the present invention, the peel strength F between the oily coating and the base film is 1 It is 3N / m~10N / m.

[0015] Preferably, the pore size L of the porous inorganic filler is 20 nm to 55 nm.

[0016] Preferably, the particle size of the porous inorganic filler is 100 nm to 600 nm.

[0017] Preferably, the porous inorganic filler includes at least one of porous alumina, porous boehmite, porous barium sulfate, porous aluminum sulfate, porous titanium dioxide, porous aluminum nitride, porous magnesium nitride, porous magnesium hydroxide, porous molybdenum disulfide or porous barium titanate.

[0018] Preferably, the porous inorganic filler has a morphology of at least one of granular, flake or rod-like.

[0019] As a preferred technical solution of the present invention, the polymer material includes at least one of meta-aramid, para-aramid, polyamide or polyimide.

[0020] As a preferred technical solution of the present invention, the bonding material includes polyacrylonitrile and polyvinylidene fluoride.

[0021] Preferably, the bonding material is grafted with oxygen-containing groups.

[0022] Preferably, the bonding material includes polyacrylonitrile and polyvinylidene fluoride modified by sodium dodecyl sulfate.

[0023] It should be noted that the polyacrylonitrile and polyvinylidene fluoride modified with sodium dodecyl sulfate refer to a mixture of polyacrylonitrile and polyvinylidene fluoride that are both modified with sodium dodecyl sulfate and are grafted with oxygen-containing groups. The specific modification process includes: preparing a tert-butyl alcohol solution of sodium dodecyl sulfate with a mass concentration of 3±0.2%, stirring polyacrylonitrile and polyvinylidene fluoride in the solution at room temperature for 0.2 to 0.8 hours, preferably 0.5 hours, and then washing with water and drying to obtain polyacrylonitrile and polyvinylidene fluoride modified with sodium dodecyl sulfate.

[0024] As a preferred technical solution of the present invention, the thickness of the oily coating is denoted as H 1 , H 1 1μm~5μm.

[0025] Preferably, the air permeability of the oily coating is 10s / 100cc to 70s / 100cc.

[0026] It should be noted that the air permeability refers to the area of ​​6.45 cm2 that 100 mL of air can pass through under a pressure of 1.21 kPa. 2 The time required for the diaphragm.

[0027] Preferably, the bonding force between the oily coating and the oily coating of another composite membrane (or membrane to membrane) is denoted as F 2 , F 2 It is 13N / m~50N / m.

[0028] It should be noted that the adhesion of the diaphragm to the diaphragm is directly proportional to the adhesion of the oily coating to the positive electrode. 2 The higher the value is, the stronger the adhesion between the oily coating and the positive electrode sheet is.

[0029] As a preferred technical solution of the present invention, the oily coating includes, by weight, 20 to 25 parts of the porous inorganic filler, 80 to 100 parts of the polymer material and 50 to 100 parts of the adhesive material.

[0030] Preferably, the material of the base film includes at least one of polyethylene (PE), polypropylene (PP), polyimide (PI) or aramid.

[0031] Preferably, the base film has a thickness of 3 μm to 20 μm.

[0032] Preferably, the base film has a pore size of 15 nm to 120 nm, a porosity of 25% to 65%, and an air permeability of 50s / 100cc to 500s / 100cc.

[0033] As a preferred technical solution of the present invention, the oily coating also includes an ion conductive material.

[0034] Preferably, the ion conductive material includes at least one of lithium germanium aluminum phosphate, lithium lanthanum titanate or lithium thiophosphate.

[0035] Preferably, the particle size of the ion conductive material is 600 nm to 1100 nm.

[0036] Preferably, the ionic conductivity of the ion conductive material is 1×10 -4 S / cm~1×10 -2 S / cm.

[0037] Preferably, the oily coating comprises 0.8 to 1.2 parts of the ion conductive material by mass.

[0038] As a preferred technical solution of the present invention, the composite membrane further comprises a water-based coating disposed on the other side of the base membrane away from the oily coating.

[0039] As a preferred technical solution of the present invention, the water-based coating includes inorganic particles, a glue layer material, a binder, a dispersant and a wetting agent.

[0040] As a preferred technical solution of the present invention, the inorganic particles include at least one of zirconium oxide, zirconium nitride, zirconium titanate, zirconium silicide or zirconium boride.

[0041] Preferably, the morphology of the inorganic particles includes at least one of granular, flake or rod-like.

[0042] Preferably, the particle size of the inorganic particles is 100 nm to 1200 nm.

[0043] As a preferred technical solution of the present invention, the adhesive layer material includes polyolefin materials and / or hydrogenated nitrile rubber (HNBR).

[0044] Preferably, the polyolefin material includes at least one of polyethylene microspheres, polypropylene microspheres or polybutylene microspheres.

[0045] Preferably, the glass transition temperature of the adhesive layer material is -20°C to 70°C.

[0046] Preferably, the particle size D of the glue layer material is 10 Particle size D is ≥1.3μm, 2.8μm≤ 50 ≤7.1μm, particle size D 90 ≤11.2μm, particle size D 99 ≤13μm.

[0047] As a preferred technical solution of the present invention, the adhesive includes at least one of acrylic material, acrylate material or acrylamide material.

[0048] Preferably, the acrylic material includes sodium acrylate or polyacrylic acid derivatives, etc.; the acrylate material includes methyl methacrylate, butyl acrylate or 2-ethylhexyl acrylate, etc.; the acrylamide material includes polyacrylamide, etc.

[0049] Preferably, the glass transition temperature of the binder is 50°C to 270°C.

[0050] As a preferred technical solution of the present invention, the thickness of the water-based coating is denoted as H 2 , H 2 1μm~3μm.

[0051] Preferably, the particle size D of the glue layer material is 50 The thickness H of the aqueous coating 2 The relationship is: 0.8≤D 50 / H 2 ≤4.2.

[0052] As a preferred technical solution of the present invention, the wetting agent includes at least one of a polyether material, a siloxane material and an enol material.

[0053] Preferably, the polyether material includes polyethylene glycol or polyoxyethylene ether, etc.; the siloxane material includes polydimethylsiloxane, etc.; the enol material includes nonylphenol polyoxyethylene ether, fatty alcohol polyoxyethylene ether or alkenyl succinate sulfonate, etc.

[0054] As a preferred technical solution of the present invention, the dispersant includes at least one of n-butanol, tert-butanol or ethanol.

[0055] Preferably, the aqueous coating comprises, by mass, 78 to 92 parts of inorganic particles, 3 to 16 parts of adhesive layer materials, 2.7 to 6 parts of binder, 0.25 to 1 part of wetting agent and 0.1 to 0.5 part of dispersant.

[0056] In a second aspect, the present invention provides a method for preparing the composite diaphragm according to the first aspect, the preparation method comprising:

[0057] An oily coating slurry is prepared and oily coating is performed on one surface of the base film to form an oily coating to obtain the composite diaphragm.

[0058] As described above, the present invention has found through research that when the inorganic filler in the oily coating is porous, the size of its pore size can affect the peel strength between the oily coating and the base film. Based on this, a new method for preparing and working the diaphragm is proposed, that is, the oily coating is still directly formed on the base film by a coating method to obtain the diaphragm, which retains the advantages of the preparation method of being simple and convenient, easy to prepare, and easy to store, transport and assemble, and avoids the adverse effects of directly forming a coating on the positive electrode sheet on the energy density and electrochemical performance of the battery. At the same time, the oily coating can be fully transferred to the surface of the positive electrode sheet through a hot pressing process during the assembly and manufacturing process of devices such as batteries, which is equivalent to transferring and setting a layer of high heat-resistant film on the surface of the positive electrode sheet, and also retains the advantages and characteristics of the working method, which effectively avoids the isolation failure caused by the shrinkage and rupture of the overall diaphragm due to changes in the base film under extreme conditions such as high temperature, and further effectively avoids the occurrence of thermal runaway, combustion and explosion problems, and greatly improves the safety of the battery. Therefore, the composite diaphragm obtained by the preparation method belongs to a high-safety diaphragm.

[0059] As a preferred technical solution of the present invention, the oily coating slurry includes an organic solvent, and the organic solvent includes at least one of N,N-dimethylacetamide (DMAc), N-methylpyrrolidone (NMP), N,N-dimethylformamide (DMF) or dimethyl sulfoxide (DMSO).

[0060] As a preferred technical solution of the present invention, the oily coating slurry also includes a co-solvent for promoting the dissolution of the polymer material, and the co-solvent includes calcium chloride (CaCl 2 ), at least one of lithium chloride (LiCl) or potassium chloride (KCl).

[0061] Preferably, the mass of the co-solvent accounts for 3.5% to 6% of the total mass of the oily coating slurry.

[0062] As a preferred technical solution of the present invention, the solid content of the oily coating slurry is 2% to 8%, and the viscosity is 30cps to 60cps.

[0063] As a preferred technical solution of the present invention, the oily coating process includes, in sequence, unwinding the base film, coating with the oily coating slurry, over-solidification molding, washing and drying.

[0064] As a preferred technical solution of the present invention, the preparation method also includes preparing a water-based coating slurry, and after forming the oily coating, without winding up, directly applying a water-based coating on the other side of the base film away from the oily coating to form a water-based coating to obtain the composite diaphragm.

[0065] Preferably, the aqueous coating slurry comprises an aqueous solvent, and the aqueous solvent comprises water.

[0066] Preferably, the solid content of the aqueous coating slurry is 27% to 33%, and the viscosity is 10 cps to 80 cps.

[0067] Preferably, the coating surface density of the adhesive layer material in the water-based coating is 0.08 g / m 2 ~0.56g / m 2 .

[0068] In a third aspect, the present invention provides a method for manufacturing a battery, the manufacturing method comprising:

[0069] Providing the composite diaphragm described in the first aspect or the composite diaphragm obtained by the preparation method described in the second aspect, and providing a positive electrode sheet, a negative electrode sheet and an electrolyte; assembling the positive electrode sheet, the negative electrode sheet and the composite diaphragm into a shape, wherein the oily coating of the composite diaphragm faces and contacts the positive electrode sheet, to obtain an electrode group;

[0070] The electrode group is firstly hot-pressed to transfer the oily coating on the composite diaphragm to the positive electrode sheet, and then packaged, baked and injected with liquid in sequence to obtain the battery.

[0071] As a preferred technical solution of the present invention, the assembly molding process includes a lamination process or a winding process.

[0072] As a preferred technical solution of the present invention, the temperature of the hot pressing is 60°C to 90°C, the surface pressure is 0.5MPa to 3MPa, and the time is 25s to 240s.

[0073] As a preferred technical solution of the present invention, the baking temperature is 95° C. to 105° C., the time is 8 h to 12 h, and the baking causes the oily coating to be transferred from the diaphragm to the positive electrode plate.

[0074] As a preferred technical solution of the present invention, the manufacturing method further comprises post-processing the obtained battery, and the post-processing comprises sequentially performing pre-charging, formation and capacity division.

[0075] As a preferred technical solution of the present invention, the battery includes a square shell battery.

[0076] As a preferred technical solution of the present invention, the positive electrode plate includes at least one of lithium cobalt oxide, lithium manganese oxide, ternary materials, lithium iron phosphate, lithium iron manganese phosphate or lithium-rich manganese-based materials, preferably including at least lithium iron phosphate.

[0077] In a fourth aspect, the present invention provides a battery, wherein the battery is obtained according to the manufacturing method described in the third aspect.

[0078] Compared with the prior art solutions, the present invention has at least the following beneficial effects:

[0079] (1) The inorganic filler used in the oily coating of the composite diaphragm of the present invention has a porous structure. By limiting the specific pore size, the contact area between the porous inorganic filler and the base film is reduced, thereby reducing the peel strength between the oily coating and the base film. During the assembly and manufacturing process of the battery, the oily coating can be transferred to the positive electrode plate by hot pressing, and the transfer rate is greater than 99.0%, basically achieving complete transfer, which is consistent with the isolation effect of directly forming the oily coating on the positive electrode plate. It avoids the isolation failure caused by the shrinkage and rupture of the entire diaphragm due to the change of the base film under extreme working conditions such as high temperature, further effectively avoiding the occurrence of thermal runaway, combustion and explosion problems, greatly improving the safety of the battery, and avoiding the impact on the electrochemical properties such as the capacity and energy density of the positive electrode plate.

[0080] (2) In the present invention, the adhesive material in the oily coating is modified so that it is grafted with oxygen-containing groups and has self-crosslinking properties. Through the baking heat treatment in the subsequent battery assembly manufacturing process, it can undergo a cross-linking reaction with the oxygen-containing groups on the surface of the positive electrode plate, thereby further improving the adhesion. The hardness of the battery cell is further improved after baking, which is beneficial to maintaining the coverage of the oily coating on the positive electrode plate after liquid injection, making it basically equivalent to the transfer rate after hot pressing, thereby ensuring the integrity and stability of the oily coating.

[0081] (3) In the present invention, a water-based coating is provided on the other side of the composite diaphragm away from the oily coating, and the negative electrode is bonded to the glue layer material in the water-based coating, which is beneficial for the adhesion of the two. The particle size of the glue layer material and the thickness of the water-based coating are controlled to increase the infiltration space, which is beneficial for the storage of the electrolyte and is beneficial for promoting the effect of no lithium precipitation on the interface after the battery cell is fully charged.

[0082] (4) In the present invention, the preparation method of the diaphragm is a solution in which oily and aqueous coatings are completed on-line at one time, i.e., oil-water continuous coating, which can avoid the complicated process of multiple winding and unwinding, facilitate large-scale continuous production, and help reduce costs. DETAILED DESCRIPTION

[0083] The technical solution of the present invention is further described below by specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.

[0084] In a specific embodiment, the present invention provides a composite membrane, the composite membrane comprising a base membrane, and also comprising an oily coating disposed on one side surface of the base membrane; the oily coating comprises a porous inorganic filler, a polymer material, and an adhesive material; the pore size of the porous inorganic filler is denoted as L, and the peel strength between the oily coating and the base membrane is denoted as F 1 , then 170×10 -9 N≤L×F 1 ≤230×10 -9 N, for example L×F 1 Can be 170×10 -9 N, 175×10 - 9 N, 180×10 -9 N, 185×10 -9 N, 190×10 -9 N, 195×10 -9 N, 200×10 -9 N, 205×10 -9 N, 210×10 -9 N, 215×10 -9 N, 220×10 -9 N, 225×10 -9 N or 230×10 -9 N et al.

[0085] In one embodiment, the peel strength F between the oily coating and the base film is 1 It is 3N / m to 10N / m, for example, 3N / m, 3.5N / m, 4N / m, 4.5N / m, 5N / m, 5.5N / m, 6N / m, 6.5N / m, 7N / m, 7.5N / m, 8N / m, 8.5N / m, 9N / m, 9.5N / m or 10N / m, etc.

[0086] In one embodiment, the pore size L of the porous inorganic filler is 20 nm to 55 nm, for example, 20 nm, 23 nm, 25 nm, 28 nm, 30 nm, 32 nm, 35 nm, 38 nm, 40 nm, 42 nm, 45 nm, 48 nm, 50 nm, 52 nm or 55 nm.

[0087] It should be noted that the pore size L of the porous inorganic filler refers to the range from the minimum pore size to the maximum pore size, and the two end values ​​of the range value can be reasonably adjusted between 20nm and 55nm to meet the requirements of 170×10 -9 N≤L×F 1 ≤230×10 -9 N.

[0088] In one embodiment, the particle size of the porous inorganic filler is 100nm to 600nm, for example, 100nm, 130nm, 150nm, 180nm, 200nm, 250nm, 280nm, 300nm, 320nm, 350nm, 380nm, 400nm, 420nm, 450nm, 480nm, 500nm, 520nm, 550nm, 580nm or 600nm.

[0089] In the present invention, when the pore size of the porous inorganic filler is determined, the particle size of the porous inorganic filler also has a certain influence on the peel strength between the oily coating and the base film. It is preferred to further use particles with smaller particle sizes to further reduce the peel strength between the oily coating and the base film.

[0090] In one embodiment, the porous inorganic filler includes at least one of porous alumina, porous boehmite, porous barium sulfate, porous aluminum sulfate, porous titanium dioxide, porous aluminum nitride, porous magnesium nitride, porous magnesium hydroxide, porous molybdenum disulfide or porous barium titanate. For example, typical combination examples include a combination of porous alumina and porous boehmite, a combination of porous barium sulfate and porous aluminum sulfate, a combination of porous alumina and porous titanium dioxide, a combination of porous alumina and porous aluminum nitride, a combination of porous aluminum nitride and porous magnesium nitride, a combination of porous magnesium nitride and porous magnesium hydroxide, or a combination of porous molybdenum disulfide and porous barium titanate, etc.

[0091] In one embodiment, the porous inorganic filler has a morphology of at least one of granular, flake or rod-like. For example, typical combination examples include a combination of granular and flake-like, a combination of granular and rod-like, or a combination of flake-like and rod-like.

[0092] In one embodiment, the polymer material includes at least one of meta-aramid, para-aramid, polyamide or polyimide. For example, typical combination examples include a combination of meta-aramid and para-aramid, a combination of meta-aramid and polyamide, a combination of meta-aramid and polyimide, or a combination of polyamide and polyimide.

[0093] In one embodiment, the bonding material includes polyacrylonitrile and polyvinylidene fluoride.

[0094] In one embodiment, the bonding material is grafted with oxygen-containing groups.

[0095] In one embodiment, the bonding material includes polyacrylonitrile and polyvinylidene fluoride modified by sodium dodecyl sulfate.

[0096] Usually, the assembly and manufacturing process of the battery will be injected with electrolyte into the battery cell. This process will cause the adhesion of the oily coating transferred by hot pressing to decrease, and it may be peeled off from the positive electrode. To this end, the present invention preferably uses an adhesive material grafted with oxygen-containing groups in the oily coating, so that the adhesive material has a self-crosslinking property, and then in the assembly and manufacturing process of the battery, such as the baking step, under the cooperation of suitable heat treatment conditions, the cross-linking reaction with the oxygen-containing groups on the surface of the positive electrode can be activated, so that the oily coating and the surface of the positive electrode are further riveted, and the adhesion between the oily coating and the positive electrode and the hardness of the battery cell after baking are improved, and the oily coating is effectively ensured to still fully and stably cover the positive electrode after injection, that is, the coverage rate of the oily coating on the positive electrode after injection is maintained, so that it is basically equivalent to the transfer rate of the oily coating after hot pressing, thereby achieving a good effect of isolating the positive and negative electrodes.

[0097] It is understood that the grafting refers to the modification on the main chain, and illustratively, the oxygen-containing groups include hydroxyl groups, carboxyl groups, sulfonic acid groups, etc. The grafting method can be to graft-modify the polymer monomers and then polymerize them to form a polymer material.

[0098] It should be noted that the present invention does not limit the positive electrode plate to be modified or optimized before it can work with the grafted modified adhesive material. Because the positive electrode active materials are usually oxide-containing materials, such as ternary materials and lithium iron phosphate, the positive electrode active materials themselves can cooperate with the adhesive material grafted with oxygen-containing groups to undergo cross-linking reaction. Therefore, the positive electrode active materials and positive electrode plates used in the prior art are applicable to the present invention. Of course, the adhesive material grafted with oxygen-containing groups can also be used to replace the conventional binder in the positive electrode plate as appropriate.

[0099] In one embodiment, the oxygen-containing group includes a hydroxyl group, a carboxyl group, a sulfonic acid group, or the like.

[0100] In one embodiment, the grafting method may be to graft-modify the polymer monomer and then polymerize it to form a polymer material.

[0101] In one embodiment, the thickness of the oily coating is denoted as H. 1 , H 1 It is 1μm to 5μm, for example, 1μm, 1.3μm, 1.5μm, 1.8μm, 2μm, 2.2μm, 2.5μm, 2.8μm, 3μm, 3.2μm, 3.5μm, 3.8μm, 4μm, 4.3μm, 4.5μm, 4.8μm or 5μm, etc.

[0102] In one embodiment, the air permeability of the oily coating is 10s / 100cc to 70s / 100cc, for example, 10s / 100cc, 15s / 100cc, 20s / 100cc, 25s / 100cc, 30s / 100cc, 35s / 100cc, 40s / 100cc, 45s / 100cc, 50s / 100cc, 55s / 100cc, 60s / 100cc, 65s / 100cc or 70s / 100cc, etc.

[0103] In one embodiment, the bonding force between the oily coating and another oily coating of the composite membrane is denoted by F 2 , F 2 It is 13N / m to 50N / m, for example, 13N / m, 15N / m, 18N / m, 20N / m, 23N / m, 25N / m, 28N / m, 30N / m, 32N / m, 35N / m, 38N / m, 40N / m, 42N / m, 45N / m, 48N / m or 50N / m, etc.

[0104] In one embodiment, the oily coating comprises 20 to 25 parts of the porous inorganic filler, such as 20, 20.3, 20.5, 20.8, 21, 21.2, 21.5, 21.8, 22, 22.3, 22.5, 22.8, 23, 23.2, 23.5, 23.8, 24, 24.2, 24.5, 24.8 or 25 parts by mass; 80 to 100 parts of the polymer material, such as 80, 81.3, 82.5, 83.8, 84.5, 85.8, 86.3, 87.5, 88.8, 89.3 parts, 90.8 parts, 91.5 parts, 92.3 parts, 93.8 parts, 94.5 parts, 95.3 parts, 96.8 parts, 97.5 parts, 98.3 parts, 99.3 parts or 100 parts, etc.; and 50 to 100 parts of bonding materials, for example 50.8 parts, 52.5 parts, 53.3 parts, 55.8 parts, 58.5 parts, 60.3 parts, 62.8 parts, 63.5 parts, 65.3 parts, 68.8 parts, 70.5 parts, 72.3 parts, 75.8 parts, 78.5 parts, 80.3 parts, 82.8 parts, 85.5 parts, 88.3 parts, 90.8 parts, 93.5 parts, 95.3 parts, 98 parts or 100 parts, etc.

[0105] In one embodiment, the base film includes at least one of polyethylene (PE), polypropylene (PP), polyimide (PI) or aramid. For example, typical combination examples include a combination of PE and PP, a combination of PE and PI, a combination of PI and aramid, a combination of PE and aramid, a combination of PI and PP, or a combination of PE and PP.

[0106] In one embodiment, the base film has a thickness of 3 μm to 20 μm, for example, 3 μm, 4 μm, 5 μm, 6 μm, 7 μm, 8 μm, 9 μm, 10 μm, 11 μm, 12 μm, 13 μm, 14 μm, 15 μm, 16 μm, 17 μm, 18 μm, 19 μm or 20 μm, etc.

[0107] In one embodiment, the pore size of the base membrane is 15nm to 120nm, for example, 15nm, 25nm, 30nm, 35nm, 40nm, 45nm, 50nm, 55nm, 60nm, 65nm, 70nm, 75nm, 80nm, 85nm, 90nm, 95nm, 100nm, 105nm, 110nm, 115nm or 120nm, etc.; the porosity is 25% to 65%, and the air permeability is 50s / 100cc to 500s / 100cc.

[0108] It should be noted that the pore size of the base membrane refers to the range of the minimum pore size to the maximum pore size, and is not the average pore size or a certain pore size limit value.

[0109] In one embodiment, the oily coating further comprises an ionically conductive material.

[0110] In one embodiment, the ion conductive material includes at least one of lithium germanium aluminum phosphate, lithium lanthanum titanium oxide or lithium thiophosphate. For example, typical combination examples include a combination of lithium lanthanum titanium oxide and lithium germanium aluminum phosphate, a combination of lithium lanthanum titanium oxide and lithium thiophosphate, or a combination of lithium thiophosphate and lithium germanium aluminum phosphate.

[0111] In one embodiment, the particle size of the ion conductive material is 600 nm to 1100 nm, for example, 600 nm, 650 nm, 700 nm, 750 nm, 800 nm, 850 nm, 900 nm, 950 nm, 1000 nm, 1050 nm or 1100 nm.

[0112] In one embodiment, the ionic conductivity of the ion conductive material is 1×10 -4 S / cm~1×10 -2 S / cm, for example 1×10 -2 S / cm, 9×10 -3 S / cm, 7×10 -3 S / cm, 5×10 -3 S / cm, 3×10 -3 S / cm, 1×10 -3 S / cm, 9×10 -4 S / cm, 8×10 -4 S / cm, 6×10-4 S / cm, 4×10 -4 S / cm, 2×10 -4 S / cm or 1×10 -4 S / cm, etc.

[0113] In one embodiment, the oily coating includes 0.8 to 1.2 parts of the ion conductive material, such as 0.8, 0.83, 0.85, 0.88, 0.9, 0.92, 0.95, 0.98, 1, 1.02, 1.06, 1.09, 1.1, 1.13, 1.15, 1.18 or 1.2 parts, etc., by mass.

[0114] In one embodiment, the composite membrane further comprises a water-based coating disposed on the other side of the base film away from the oily coating.

[0115] In the present invention, the oily coating of the composite diaphragm is opposite to the positive electrode plate, and the other side of the base film is preferably provided with a water-based coating to bond with the negative electrode plate, thereby optimizing the interface with the negative electrode, increasing the wetting space, and improving the problem of lithium plating at the battery cell interface.

[0116] In one embodiment, the aqueous coating comprises inorganic particles, a glue layer material, a binder, a dispersant and a wetting agent.

[0117] In one embodiment, the inorganic particles include at least one of zirconium oxide, zirconium nitride, zirconium titanate, zirconium silicide or zirconium boride. For example, typical combination examples include a combination of zirconium oxide and zirconium nitride, a combination of zirconium oxide and zirconium titanate, a combination of zirconium oxide and zirconium silicide, a combination of zirconium oxide and zirconium boride, a combination of zirconium nitride and zirconium titanate, a combination of zirconium nitride and zirconium silicide, a combination of zirconium nitride and zirconium boride, a combination of zirconium titanate and zirconium silicide, a combination of zirconium titanate and zirconium boride, or a combination of zirconium silicide and zirconium boride.

[0118] In one embodiment, the morphology of the inorganic particles includes at least one of granular, flake or rod-like. For example, typical combination examples include a combination of granular and flake-like, a combination of granular and rod-like, or a combination of flake-like and rod-like.

[0119] In one embodiment, the particle size of the inorganic particles is 100 nm to 1200 nm, for example, 100 nm, 200 nm, 300 nm, 400 nm, 500 nm, 600 nm, 700 nm, 800 nm, 900 nm, 1000 nm, 1100 nm or 1200 nm.

[0120] It should be noted that, except for specially specified particle size values, the particle size values ​​of the porous inorganic filler, the particle size values ​​of the ion conductive material, and the particle size values ​​of the inorganic particles in the present invention are all range values ​​represented by the minimum size of the actual particles (including primary particles or agglomerated secondary particles) to the maximum size of the actual particles, and are not the average particle size or other particle size limit values.

[0121] In one embodiment, the adhesive layer material includes polyolefin material and / or hydrogenated nitrile rubber.

[0122] In one embodiment, the polyolefin material includes at least one of polyethylene microspheres, polypropylene microspheres or polybutylene microspheres.

[0123] In one embodiment, the glass transition temperature (Tg) of the adhesive layer material is -20°C to 70°C, for example, -20°C, -19°C, -18°C, -16°C, -15°C, -13°C, 10°C, -8°C, -5°C, 0°C, 5°C, 10°C, 15°C, 20°C, 25°C, 30°C, 35°C, 40°C, 45°C, 50°C, 55°C, 60°C, 65°C or 70°C, etc.

[0124] In one embodiment, the particle size D of the glue layer material is 10 ≥1.3μm, such as 1.3μm, 1.5μm, 1.8μm, 2μm, 2.2μm, 2.5μm or 2.76μm, etc.; 2.8μm≤particle size D 50 ≤7.1μm, such as 2.8μm, 3.3μm, 3.5μm, 3.8μm, 4μm, 4.2μm, 4.5μm, 4.8μm, 5μm, 5.2μm, 5.5μm, 5.8μm, 6μm, 6.2μm, 6.5μm, 6.8μm or 7.1μm, etc.; particle size D 90 ≤11.2μm, such as 7.3μm, 7.8μm, 8μm, 8.5μm, 8.8μm, 9μm, 9.2μm, 9.5μm, 9.8μm, 10μm, 10.2μm, 10.5μm, 10.8μm, 11μm or 11.2μm, etc.; particle size D 99 ≤13μm, for example, 11.5μm, 11.8μm, 12μm, 12.2μm, 12.5μm, 12.8μm or 13μm, etc.

[0125] In one embodiment, the adhesive includes at least one of acrylic material, acrylate material and acrylamide material. For example, typical combination examples include a combination of acrylic material and acrylate material, a combination of polyacrylic acid material and acrylamide material, or a combination of acrylamide material and acrylate material.

[0126] In one embodiment, the glass transition temperature (Tg) of the binder is 50°C to 270°C, for example, 50°C, 60°C, 80°C, 90°C, 100°C, 120°C, 140°C, 160°C, 180°C, 200°C, 220°C, 230°C, 250°C or 270°C.

[0127] In one embodiment, the thickness of the aqueous coating is denoted as H. 2 , H 2 It is 1μm to 3μm, for example, 1μm, 1.3μm, 1.5μm, 1.8μm, 2μm, 2.2μm, 2.5μm, 2.8μm or 3μm.

[0128] In one embodiment, the particle size D of the glue layer material is 50 The thickness H of the aqueous coating 2 The relationship is: 0.8≤D 50 / H 2 ≤4.2, e.g. D 50 / H 2 It can be 0.8, 1, 1.2, 1.5, 1.8, 2, 2.2, 2.5, 2.8, 3, 3.2, 3.5, 3.8, 4 or 4.2, etc.

[0129] In the present invention, in order to ensure that the water-based coating can provide a wetting space, D 50 and H 2 The above relationship must be satisfied. 50 / H 2 <0.8, the larger (larger than inorganic materials) glue layer material particles are exposed to a low height of the water-based coating, which cannot achieve the effect of bonding and gap creation to enhance the infiltration space; and if D 50 / H 2 >4.2, the adhesive layer material with larger particles is too high to be exposed from the water-based coating and is easy to fall off, and the stable bonding effect cannot be achieved, resulting in serious powder loss of the diaphragm.

[0130] In one embodiment, the wetting agent includes at least one of a polyether material, a siloxane material and an enol material. For example, typical combination examples include a combination of a polyether material and a siloxane material, a combination of a polyether material and an enol material, or a combination of an enol material and a siloxane material.

[0131] In one embodiment, the dispersant includes at least one of n-butanol, tert-butanol or ethanol. For example, typical combination examples include a combination of n-butanol and tert-butanol, a combination of n-butanol and ethanol, or a combination of ethanol and tert-butanol.

[0132] In one embodiment, the aqueous coating comprises, by mass, 78 to 92 parts of inorganic particles, 3 to 16 parts of adhesive layer materials, 2.7 to 6 parts of binder, 0.25 to 1 part of wetting agent and 0.1 to 0.5 parts of dispersant.

[0133] In some specific embodiments, the present invention provides a method for preparing the composite membrane described in the first aspect, the preparation method comprising: preparing an oily coating slurry, applying an oily coating on one surface of a base film to form an oily coating, and obtaining the composite membrane.

[0134] In one embodiment, the oily coating slurry includes an organic solvent, and the organic solvent includes at least one of N,N-dimethylacetamide (DMAc), N-methylpyrrolidone (NMP), N,N-dimethylformamide (DMF) or dimethyl sulfoxide (DMSO). For example, typical combination examples include a combination of N,N-dimethylacetamide and N-methylpyrrolidone, a combination of N,N-dimethylacetamide and N,N-dimethylformamide, a combination of N,N-dimethylacetamide and dimethyl sulfoxide, or a combination of N,N-dimethylformamide and dimethyl sulfoxide.

[0135] In one embodiment, the oily coating slurry further comprises a cosolvent for promoting the dissolution of the polymer material, wherein the cosolvent comprises calcium chloride (CaCl 2 ), at least one of lithium chloride (LiCl) or potassium chloride (KCl), for example, typical combination examples include a combination of calcium chloride and lithium chloride, a combination of calcium chloride and potassium chloride, or a combination of potassium chloride and lithium chloride, etc.

[0136] It is understandable that the solvent selected in the oily coating slurry should have a high solubility for the polymer material and the adhesive material. Furthermore, a co-solvent may be added to promote the dissolution of the polymer material.

[0137] In one embodiment, the mass of the co-solvent accounts for 3.5% to 6% of the total mass of the oily coating slurry, for example, 3.5%, 3.8%, 4%, 4.2%, 4.5%, 4.8%, 5%, 5.3%, 5.5%, 5.8% or 6%, etc.

[0138] In one embodiment, the solid content of the oily coating slurry is 2% to 8%, for example, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5%, 5.5%, 6%, 6.5%, 7%, 7.5% or 8%, and the viscosity is 30cps to 60cps, for example, 30cps, 33cps, 35cps, 38cps, 40cps, 43cps, 45cps, 48cps, 50cps, 52cps, 55cps, 58cps or 60cps, etc.

[0139] In one embodiment, the oil coating process includes, in sequence, unwinding a base film, coating with the oil coating slurry, over-solidification molding, washing and drying.

[0140] It should be noted that, in the present invention, when the oily coating process undergoes a washing process, the washing will remove the co-solvent, and the residual amount of the co-solvent in the oily coating can be ignored.

[0141] In one embodiment, the preparation method further includes preparing a water-based coating slurry, and after forming the oily coating, without winding up, directly applying a water-based coating on the other side of the base film away from the oily coating to form a water-based coating to obtain the composite diaphragm.

[0142] The preparation method of the diaphragm of the present invention is a scheme in which oily and aqueous coatings are completed online at one time, that is, oil-water continuous coating. The process of the preparation method includes unwinding, oily coating slurry coating, coagulation bath molding, water washing, and drying, followed by aqueous coating, and winding after the aqueous coating is dried. The traditional process needs to include unwinding, oily coating slurry coating, coagulation bath molding, water washing, drying, winding, unwinding, aqueous coating, drying and winding in sequence. From the above comparison, it can be seen that the scheme of the present invention can avoid the complex process flow of multiple winding and unwinding, which is convenient for large-scale continuous production and is conducive to reducing costs. However, it should be emphasized that the preparation method should first carry out oily coating to form an oily coating and then carry out aqueous coating. If the aqueous coating is formed first, the process steps of oily coating such as coagulation molding and water washing will affect the formed aqueous coating and even cause it to disperse and break.

[0143] It is also worth noting that in the specific implementation of oily coating and water-based coating, it is necessary to dry after wet coating in order to obtain a dry coating. In this field, the drying time is generally short, which will not affect the adhesion of the obtained oily coating and its peel strength with the base film.

[0144] In one embodiment, the aqueous coating slurry includes an aqueous solvent, and the aqueous solvent includes water.

[0145] In one embodiment, the solid content of the aqueous coating slurry is 27% to 33%, for example, 27%, 28%, 29%, 30%, 31%, 32% or 33%, and the viscosity is 10cps to 80cps, for example, 10cps, 15cps, 20cps, 25cps, 30cps, 35cps, 40cps, 45cps, 50cps, 55cps, 60cps, 65cps, 70cps, 75cps or 80cps, etc.

[0146] In one embodiment, the coating surface density of the adhesive layer material in the water-based coating is 0.08 g / m 2 ~0.56g / m 2 , for example 0.08g / m 2 , 0.1g / m 2 , 0.13g / m 2 , 0.15g / m 2 , 0.18g / m 2 , 0.2g / m 2 , 0.23g / m 2 , 0.26g / m 2 , 0.3g / m 2 , 0.35g / m 2 , 0.4g / m 2 , 0.43g / m 2 , 0.48g / m 2 , 0.5g / m 2 , 0.53g / m 2 or 0.56g / m 2+ wait.

[0147] In some specific implementation methods, the present invention provides a method for manufacturing a battery, the manufacturing method comprising: providing the composite diaphragm described in the above-mentioned embodiment, and providing a positive electrode sheet, a negative electrode sheet and an electrolyte; assembling the positive electrode sheet, the negative electrode sheet and the composite diaphragm into a shape, wherein the oily coating of the composite diaphragm faces and contacts the positive electrode sheet, to obtain a pole group; first hot pressing the pole group to transfer the oily coating on the composite diaphragm to the positive electrode sheet, and then packaging, baking and injecting liquid in sequence to obtain the battery.

[0148] In one embodiment, the assembly molding process includes a lamination process or a winding process.

[0149] In one embodiment, the lamination process includes a Z-shaped lamination or a thermal lamination (fly lamination) process.

[0150] In one embodiment, the hot pressing temperature is 60°C to 90°C, for example, 60°C, 65°C, 70°C, 75°C, 80°C, 85°C or 90°C; the surface pressure is 0.5MPa to 3MPa, for example, 0.5MPa, 0.8MPa, 1MPa, 1.2MPa, 1.5MPa, 1.8MPa, 2MPa, 2.3MPa, 2.5MPa, 2.8MPa or 3MPa; the time is 25s to 240s, for example, 25s, 50s, 75s, 100s, 120s, 140s, 160s, 180s, 200s, 220s or 240s.

[0151] It should be noted that in the present invention, the parameters of the hot pressing process should satisfy the assembly and molding of the electrode group on the one hand, and the transfer of the oily coating from the base film to the positive electrode sheet on the other hand. In theory, the larger the parameters of the hot pressing, the more conducive to the transfer of the oily coating. However, if the parameters are too large, it will cause pressure damage to the electrode group and easily cause the negative electrode to drop. Therefore, the parameters of the hot pressing should be reasonably adjusted according to the peel strength between the oily coating and the base film.

[0152] In one embodiment, the baking temperature is 95°C to 105°C, for example, 95°C, 96°C, 97°C, 98°C, 99°C, 100°C, 101°C, 102°C, 103°C, 104°C or 105°C, etc.; the baking time is 8h to 12h, for example, 8h, 8.3h, 8.5h, 8.8h, 9h, 9.2h, 9.5h, 9.8h, 10h, 10.2h, 10.5h, 10.8h, 11h, 11.2h, 11.5h, 11.8h or 12h, etc., and the baking transfers the oily coating from the diaphragm to the positive electrode sheet.

[0153] As described above, in the present invention, the oily coating has been transferred from the base film to the positive electrode plate in a process before baking, such as a hot pressing process. Therefore, in actual operation, the self-crosslinking activation temperature of the adhesive material grafted with oxygen-containing groups in the oily coating should be controlled and selected based on the baking temperature of the battery cell, preferably at 95°C to 100°C, so that the oily coating and the surface oxygen-containing groups of the positive electrode plate undergo cross-linking reaction to achieve the effect and purpose of enhancing the bonding force and maintaining the coverage and stability of the transferred oily coating.

[0154] In one embodiment, based on the baking temperature of the battery cell, the self-crosslinking activation temperature of the adhesive material grafted with oxygen-containing groups in the oily coating is controlled and selected, preferably at 95°C to 100°C, so that the oily coating and the surface oxygen-containing groups of the positive electrode plate undergo a crosslinking reaction.

[0155] In one embodiment, the manufacturing method further comprises post-processing the obtained battery, wherein the post-processing comprises sequentially performing pre-charging, formation and capacity separation.

[0156] In one embodiment, the battery comprises a square-cased battery.

[0157] It is worth noting that, generally, compared with cylindrical batteries and soft-pack batteries, square-shell batteries require a hot pressing process. However, for other types of batteries, appropriate hot pressing and heat treatment processes can be added to the assembly and manufacturing process of the battery as appropriate, with the understanding of the purpose of the present invention, to achieve the transfer of the oily coating, or further achieve the cross-linking riveting effect between the oily coating and the positive electrode sheet, so that the oily coating can stably cover the surface of the positive electrode sheet and play an isolating role.

[0158] In one embodiment, the positive electrode active material of the positive electrode plate includes at least one of lithium cobalt oxide, lithium manganese oxide, ternary materials, lithium iron phosphate, lithium iron manganese phosphate or lithium-rich manganese-based materials, preferably at least lithium iron phosphate.

[0159] As mentioned above, it is worth noting that the present invention does not specifically limit the specific material selection of the positive electrode sheet, the negative electrode sheet and the electrolyte in the battery. The positive electrode active material, the negative electrode active material, the binder, the conductive agent, the pulping solvent, the lithium salt, the electrolyte solvent and the electrolyte additive used in the art are all applicable to the present invention.

[0160] In some specific embodiments, the present invention provides a battery, wherein the battery is obtained according to the manufacturing method described in the above embodiment.

[0161] Example 1

[0162] This embodiment provides a composite diaphragm, the composite diaphragm comprising:

[0163] Basement membrane, the basement membrane is made of aramid, has a thickness of 12 μm, a pore size of 56 nm, a porosity of 35%, and an air permeability of 350 s / 100 cc;

[0164] The oily coating is arranged on one side surface of the base film; the oily coating comprises 23 parts of porous inorganic filler, 90 parts of polymer material, 70 parts of bonding material and 1 part of ion conductive material by weight; the porous inorganic filler is porous titanium dioxide, which is granular in shape, with a particle size of 400nm and a pore size L of 33nm; the bonding material comprises polyacrylonitrile and polyvinylidene fluoride grafted with oxygen-containing groups by sodium dodecyl sulfate; the polymer material comprises polyimide; the ion conductive material comprises lithium lanthanum titanium oxide, with a particle size of 850nm and an ion conductivity of 5×10 -3 S / cm; Peel strength F between the oily coating and the base film 1 is 6N / m, then L×F 1 =198×10 -9 N; the thickness of the oily coating H 1 The adhesion force F between the oily coating and the oily coating of the composite membrane is 3 μm and the air permeability is 44 s / 100 cc. 2 33.2N / m;

[0165] The water-based coating is arranged on the surface of the other side of the base film away from the oily coating; the water-based coating comprises 86 parts of inorganic particles, 9 parts of adhesive layer materials, 4 parts of binders, 0.68 parts of dispersants and 0.32 parts of wetting agents by weight; the inorganic particles are granular zirconium nitride with a particle size of 600nm; the adhesive layer material is polyethylene microspheres with a glass transition temperature of 35°C and a particle size of D 10 =1.5μm, D 50 =5.4μm, D 90 =9μm, D 99 =12.8 μm; the binder is methyl methacrylate, and its glass transition temperature is 105°C; the wetting agent includes polyethylene glycol; the dispersant includes n-butanol; the thickness of the water-based coating is H 2 is 2.4 μm, then the particle size D of the adhesive layer material 50 The thickness H of the aqueous coating 2 There is D 50 / H 2 =2.25.

[0166] This embodiment also provides a method for preparing the composite diaphragm, the method comprising:

[0167] S1. Prepare oily coating slurry: weigh porous inorganic filler, polymer material, adhesive material, ion conductive material, solvent and co-solvent, mix them, and obtain oily coating slurry; the solvent is N,N-dimethylformamide, and the co-solvent is calcium chloride; the mass of the co-solvent is controlled to account for 4% of the total mass of the oily coating slurry, the solid content of the oily coating slurry is 5%, and the viscosity is 45cps;

[0168] S2. Oily coating: unwinding the base film, coating one side of the base film with the oily coating slurry, and then sequentially solidifying, washing and drying to form an oily coating;

[0169] S3. Preparation of water-based coating slurry: weigh inorganic particles, adhesive layer material, binder, dispersant, wetting agent and solvent water and mix them to obtain a water-based coating slurry;

[0170] S4. Water-based coating: without winding up the diaphragm, directly apply the water-based coating slurry on the other side of the base film forming the oily coating, and control the coating surface density of the adhesive layer material in the water-based coating to 0.32 g / m 2 , and then dried to form a water-based coating to obtain a composite diaphragm.

[0171] Example 2

[0172] This embodiment provides a composite membrane, in which the pore size L of the porous inorganic filler is adjusted from 33 nm to 20 nm, so that the peeling strength F between the oily coating and the base film is 1 Adjust from 6N / m to 8.5N / m, then L×F 1 The value is 198×10 -9 N becomes 170×10 -9 N, except for the above, other conditions are exactly the same as those in Example 1.

[0173] Example 3

[0174] This embodiment provides a composite membrane, in which the pore size L of the porous inorganic filler is adjusted from 33 nm to 50 nm, so that the peeling strength F between the oily coating and the base film is 1 Adjust from 6N / m to 4.6N / m, then L×F 1 The value is 198×10 -9 N becomes 230×10 -9 N, except for the above, other conditions are exactly the same as those in Example 1.

[0175] Example 4

[0176] This embodiment provides a composite diaphragm, in which the bonding materials of the composite diaphragm are replaced by conventional unmodified polyacrylonitrile and polyvinylidene fluoride from polyacrylonitrile and polyvinylidene fluoride modified by grafting of oxygen-containing groups. Except for the above, other conditions are exactly the same as those in Embodiment 1.

[0177] Example 5

[0178] This embodiment provides a composite diaphragm, in which the bonding materials of polyacrylonitrile and polyvinylidene fluoride grafted with oxygen-containing groups are replaced with polyacrylonitrile grafted with oxygen-containing groups, and polyvinylidene fluoride grafted with oxygen-containing groups is not used. Except for the above, other conditions are exactly the same as those in Example 1.

[0179] Example 6

[0180] This embodiment provides a composite diaphragm, in which the bonding materials of the composite diaphragm are replaced by polyvinylidene fluoride grafted with oxygen-containing groups instead of polyacrylonitrile grafted with oxygen-containing groups. Polyacrylonitrile grafted with oxygen-containing groups is not used. Except for the above, other conditions are exactly the same as those in Example 1.

[0181] Example 7

[0182] This embodiment provides a composite membrane, wherein the composite membrane adjusts the particle size of the glue layer material in the water-based coating so that the particle size D of the glue layer material is 50 The thickness H of the aqueous coating 2 Relationship D50 / H 2 =0.5, except for the above, other conditions are exactly the same as those in Example 1.

[0183] Example 8

[0184] This embodiment provides a composite membrane, wherein the composite membrane adjusts the particle size of the glue layer material in the water-based coating so that the particle size D of the glue layer material is 50 The thickness H of the aqueous coating 2 Relationship D 50 / H 2 =0.8, except for the above, other conditions are exactly the same as those in Example 1.

[0185] Example 9

[0186] This embodiment provides a composite membrane, wherein the composite membrane adjusts the particle size of the glue layer material in the water-based coating so that the particle size D of the glue layer material is 50 The thickness H of the aqueous coating 2 Relationship D 50 / H 2 =4.2, except for the above, other conditions are exactly the same as those in Example 1.

[0187] Example 10

[0188] This embodiment provides a composite membrane, wherein the composite membrane adjusts the particle size of the glue layer material in the water-based coating so that the particle size D of the glue layer material is 50 The thickness H of the aqueous coating 2 Relationship D 50 / H 2 =4.5, except for the above, other conditions are exactly the same as those in Example 1.

[0189] Embodiment 11

[0190] This embodiment provides a composite diaphragm, wherein the composite diaphragm is provided with the oily coating but not the aqueous coating. Except for the above, other conditions are exactly the same as those in Embodiment 1.

[0191] Comparative Example 1

[0192] This comparative example provides a composite diaphragm, in which the porous inorganic filler is adjusted to a common inorganic filler, the composite diaphragm does not have a porous structure, and the pore size L is 0. Except for the above, other conditions are exactly the same as those in Example 1.

[0193] Comparative Example 2

[0194] This comparative example provides a composite membrane, in which the pore size L of the porous inorganic filler is adjusted from 33 nm to 12 nm, so that the peeling strength F between the oily coating and the base film is 1 Adjust from 6N / m to 12.5N / m, then L×F 1 The value is 198×10 -9 N becomes 150×10 -9 N, except for the above, other conditions are exactly the same as those in Example 1.

[0195] Comparative Example 3

[0196] This comparative example provides a composite membrane, in which the pore size L of the porous inorganic filler is adjusted from 33 nm to 100 nm, so that the peeling strength F between the oily coating and the base film is 1 Adjust from 6N / m to 2.5N / m, then L×F 1 The value is 198×10 -9 N becomes 250×10 -9 N, except for the above, other conditions are exactly the same as those in Example 1.

[0197] The bonding force F between the oily coating and another oily coating of the composite membrane in Examples 2 to 11 and Comparative Examples 1 to 3 2 Corresponding changes occur, see the results of characterization and testing for details.

[0198] Application Example 1

[0199] This application example provides a battery, wherein the battery comprises the composite separator provided by any one of Examples 1 to 16 or Comparative Examples 1 to 3, and the manufacturing method of the battery comprises:

[0200] A positive electrode sheet, a negative electrode sheet and an electrolyte are provided; the positive electrode sheet is prepared by using lithium iron phosphate, a conductive agent, a binder and the like to prepare a positive electrode slurry, the positive electrode slurry is coated on a carbon-coated aluminum foil and treated to obtain a positive electrode sheet, and the mass proportion of the positive electrode active material lithium iron phosphate in the positive electrode active layer is 96.9%; the negative electrode sheet is prepared by using artificial graphite, a conductive agent, a binder and a thickener to prepare a negative electrode slurry, the negative electrode slurry is coated on a copper foil and treated to obtain a negative electrode sheet, and the mass proportion of the negative electrode active material artificial graphite in the negative electrode active layer is 96.4%; the electrolyte is an electrolyte composed of a lithium salt, a solvent and an additive, specifically, the electrolyte includes 1.2M LiPF 6 , EC (ethylene carbonate), DMC (dimethyl carbonate) and EMC (ethyl methyl carbonate) in a volume ratio of 1:1:1, as well as 2wt% of VC (vinylene carbonate) and 1wt% of FEC (fluoroethylene carbonate).

[0201] The positive electrode sheet, the negative electrode sheet and the composite diaphragm are assembled and formed by a winding process to obtain an electrode group, wherein the oily coating faces the positive electrode sheet and the water-based coating faces the negative electrode sheet. The obtained electrode group is hot pressed at a temperature of 78°C and a surface pressure of 2MPa for 100s; then it is packaged in a square shell form, and the packaged battery cell is placed in an oven and baked at 100°C for 10h, and then the electrolyte is injected (liquid injection) and left to stand at high temperature for 24h; after the standing is completed, the pre-charging, formation and capacity division are continued in sequence to obtain the battery.

[0202] Application Example 2

[0203] This application example provides a battery, which contains the composite diaphragm provided in Example 1. In the manufacturing method of the battery, the positive electrode active material in the positive electrode plate is adjusted from lithium iron phosphate to the ternary material NCM523. Except for the above, other conditions are exactly the same as those in Application Example 1.

[0204] Application Comparative Example 1

[0205] The present application comparative example provides a battery, which uses the positive electrode plate, negative electrode plate and electrolyte in Application Example 1, and uses a diaphragm containing only the aqueous coating. The manufacturing method of the battery comprises: coating the positive electrode active layer of the positive electrode plate with an oily ceramic slurry, wherein the oily ceramic slurry is composed of a porous inorganic filler, a bonding material and a solvent, wherein the porous inorganic filler and the solvent are the same as those in Example 1, and the bonding material is polyacrylonitrile and polyvinylidene fluoride that have not been grafted with oxygen-containing groups; then drying to form a ceramic surface coating; and then assembling the positive electrode plate with the ceramic surface coating, the diaphragm containing the aqueous coating and the negative electrode plate into a battery according to the scheme of Application Example 1.

[0206] Application Comparative Example 2

[0207] The present application comparative example provides a battery, which uses the positive electrode plate, negative electrode plate and electrolyte in Application Example 2, and uses a diaphragm containing only the aqueous coating. The manufacturing method of the battery comprises: coating the positive electrode active layer of the positive electrode plate with an oily ceramic slurry, wherein the oily ceramic slurry is composed of a porous inorganic filler, a bonding material and a solvent, wherein the porous inorganic filler and the solvent are the same as those in Example 1, and the bonding material is polyacrylonitrile and polyvinylidene fluoride that have not been grafted with oxygen-containing groups; then drying to form a ceramic surface coating; and then assembling the positive electrode plate with the ceramic surface coating, the diaphragm containing the aqueous coating and the negative electrode plate into a battery according to the scheme of Application Example 2.

[0208] Characterization and Testing:

[0209] Ⅰ. Examples and Comparative Examples The obtained composite membranes were subjected to the following tests: 150°C heat shrinkage test, membrane rupture temperature test, adhesion F between the fresh membrane and the two oily coatings of the membrane 2 Test the peel strength between the oily coating and the base film F 1 test.

[0210] Ⅱ. In the application examples and comparative examples, after the electrode group is hot pressed, a part of the electrode group is taken for hipot short circuit test at 180℃, and another part of the electrode group of the same batch is taken to disassemble the electrode group to measure the transfer rate (coverage) of the oily coating on the positive electrode plate. After the battery cell is injected with liquid and left at high temperature for 24 hours, the electrode group is disassembled to measure the coverage of the oily coating on the positive electrode plate after injection. Disassemble the interface after the battery cell is divided into different capacities to observe whether the interface is abnormal.

[0211] III. The batteries obtained in the corresponding use cases and application comparison examples were subjected to hot box test, needle penetration test, and heat spread test at 25°C (normal temperature) and 60°C (high temperature).

[0212] The above results are recorded in Table 1 and Table 2.

[0213] Table 1

[0214]

[0215]

[0216] Table 2

[0217]

[0218] From Table 1 and Table 2, we can see that:

[0219] In Application Example 1 and Application Comparative Example 1, it is found that when 170×10 -9 N≤L×F 1 ≤230×10 -9 N, the coating transfer rate after hot pressing and injection is good, the 180℃ short circuit rate test is satisfied, and the safety test can be passed. When the inorganic filler is solid (no porous structure), or L×F 1 <170×10 -9 N, the effect of the inorganic filler and the heat-resistant polymer becoming a uniformly mixed phase becomes worse, and the coating peel strength increases, the coating transfer effect becomes worse, affecting the short circuit test and safety test results. When L×F 1 >230×10 -9N, the inorganic filler floats in the oily slurry, which makes the membrane adhesion worse, affects the coating transfer effect, and further affects the battery safety performance. Similarly, by comparing Application Example 2 with Application Comparative Example 2, it can be seen that the positive electrode sheet does not distinguish between iron lithium and ternary, and both positive electrode systems can achieve the effect under this scheme. Compared with the scheme of directly coating on the ternary positive electrode sheet, the safety of the battery cell is deteriorated, and this design will reduce the energy density and affect the cycle performance.

[0220] In Application Example 1 and Application Comparative Example 1, Example 1 was compared with Examples 4-6 and it was found that when conventional unmodified polyacrylonitrile and polyvinylidene fluoride were used, the coating coverage after liquid injection decreased from 99.2% after hot pressing to 90.3%, and the coverage decreased significantly, thereby deteriorating the safety performance of the battery cell; while when polyacrylonitrile and polyvinylidene fluoride modified by oxygen-containing group grafting were used, the coating transfer effect after liquid injection was slightly reduced, which did not affect the battery safety test performance.

[0221] In Application Example 1 and Application Comparative Example 1, by comparing Example 1 with Examples 7 to 10, it is found that 0.8≤D 50 / H 2 When ≤4.2, the interface can prevent lithium deposition and the battery safety test can be passed; when D 50 / H 2 When the value is less than 0.8, the large particles of glue are not exposed from the ceramic coating, and the gap cannot be formed. Lithium will be deposited on the interface, affecting the safety of the battery cell. 50 / H 2 When it is greater than 4.2, the large particles of glue are large in size and more of the ceramic coating is exposed, which will destroy the integrity of the ceramic coating, increase thermal shrinkage, and worsen the safety of the battery cell. In addition, the glue layer is prone to powdering during the manufacturing process, and the accumulated dust particles become larger, which can be introduced into the battery cell and puncture the diaphragm, further causing safety problems.

[0222] In Application Example 1 and Application Comparative Example 1, Example 1 is compared with Example 11 to find that without the provision of a water-based coating, the diaphragm lacks a glue layer on one side, and the overall bonding force deteriorates, resulting in a weakening of the hardness of the electrode group after liquid injection, which will affect the coverage of the oily coating on the positive electrode sheet after liquid injection; and there is no liquid storage space, and there is a lithium precipitation problem at the interface; without one side of the ceramic heat-resistant coating, the thermal shrinkage of the diaphragm becomes larger. Overall, the safety performance of the battery cell deteriorates.

[0223] From the above we can see that:

[0224] 1) The oil-water continuous coating diaphragm proposed in the present invention can shrink less than 5% at 150°C, the adhesion of the oily coating surface is relatively high, and the peeling strength between the coating and the base film is low, which is conducive to the transfer of the oily coating to the positive electrode after hot pressing. After the pole group is baked, the adhesive material in the oily coating has been modified and cross-linked, and the adhesion will be further improved. Therefore, the coverage of the coating on the positive electrode after hot pressing and liquid injection is greater than 99%, and it is basically completely transferred to the positive electrode, and can remain intact and stable. Even in a high temperature environment, even if the diaphragm shrinks, the oily coating has been transferred to the positive electrode, and it still plays a role in isolating the positive and negative electrodes, so the 180°C short-circuit test can be passed. In Comparative Example 1, the diaphragm has relatively poor heat resistance, and the peeling strength with the coating is high, and the diaphragm adhesion is relatively poor, resulting in a relatively poor coating transfer effect, resulting in failure of the 180°C short-circuit test and safety test.

[0225] 2) The negative electrode is bonded to the glue material in the aqueous coating of the diaphragm, which is conducive to the fit between the two, and there is space for electrolyte storage, and there is no lithium precipitation at the interface after the battery cell is fully charged. The hot box can pass 240°C, and both the needle puncture and heat spread tests are passed. In Example 16, due to the lack of one side of the aqueous coating, the thermal shrinkage of the diaphragm is worse, the coating conversion rate decreases significantly after injection, the high-temperature hipot test is short-circuited, the battery cell safety test is not passed, and there is lithium precipitation at the fully charged negative electrode interface, which seriously affects the electrical performance.

[0226] In summary, the oily and water-based continuous coating diaphragm proposed in the present invention effectively reduces the number of processing times and reduces the processing cost from a process perspective. From the perspective of diaphragm performance, the diaphragm has excellent heat resistance, and the oily coating has good diaphragm adhesion and weak peeling strength with the base film. The coating can be transferred to the positive electrode after hot pressing and injection, with a coverage rate of >99%. After the battery cell is baked, the oily coating is further riveted to the positive electrode to improve the adhesion and ensure that the oily coating is still fully covered on the electrode in the electrolyte infiltration state. And the water-based coating is bonded to the negative electrode, optimizing the interface with the negative electrode, increasing the infiltration space, and improving the problem of lithium precipitation at the interface of the battery cell. At high temperatures, although the diaphragm shrinks, the coating is still isolated from the positive and negative electrodes, greatly reducing the problem of battery cell short circuit caused by diaphragm shrinkage. The battery containing and applying the composite diaphragm described in the present invention can pass the hot box, needle puncture and heat spread tests.

[0227] The present invention illustrates the detailed structural features of the present invention through the above embodiments, but the present invention is not limited to the above detailed structural features, that is, it does not mean that the present invention must rely on the above detailed structural features to be implemented. Those skilled in the art should understand that any improvement of the present invention, equivalent replacement of the components selected by the present invention, addition of auxiliary components, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.

[0228] The preferred embodiments of the present invention are described in detail above. However, the present invention is not limited to the specific details in the above embodiments. Within the technical concept of the present invention, a variety of simple modifications can be made to the technical solution of the present invention, and these simple modifications all belong to the protection scope of the present invention.

[0229] It should be noted that the above implementation is not limited to the listed numerical point values ​​and typical combination examples. Numerical point values ​​or combination examples not listed within the above numerical range can still be selected and applied to the present invention.

[0230] It should also be noted that the various specific technical features described in the above specific embodiments can be combined in any suitable manner without contradiction. In order to avoid unnecessary repetition, the present invention will not further describe various possible combinations.

[0231] In addition, various embodiments of the present invention may be arbitrarily combined, and as long as they do not violate the concept of the present invention, they should also be regarded as the contents disclosed by the present invention.

Claims

1. A composite diaphragm, characterized in that: The invention comprises a base film and an oily coating disposed on one side of the base film; the oily coating comprises a porous inorganic filler, a polymer material and an adhesive material; the pore size of the porous inorganic filler is denoted as L, and the peel strength between the oily coating and the base film is denoted as F1. Then 170×10 -9 N≤L×F1≤230×10 -9 N.

2. The composite diaphragm according to claim 1, characterized in that: The peel strength F1 between the oily coating and the base film is 3N / m to 10N / m; Preferably, the pore size L of the porous inorganic filler is 20 nm to 55 nm; Preferably, the particle size of the porous inorganic filler is 100nm to 600nm; Preferably, the bonding material comprises polyacrylonitrile and polyvinylidene fluoride; Preferably, the bonding material is grafted with oxygen-containing groups; Preferably, the bonding material comprises polyacrylonitrile and polyvinylidene fluoride modified by sodium dodecyl sulfate; Preferably, the thickness of the oily coating is denoted as H1, and H1 is 1 μm to 5 μm; Preferably, the air permeability of the oily coating is 10s / 100cc to 70s / 100cc; Preferably, the bonding force between the oily coating and the oily coating of another composite membrane is denoted as F2, and F2 is 13N / m to 50N / m.

3. The composite diaphragm according to claim 1 or 2, characterized in that: The oily coating comprises 20 to 25 parts of the porous inorganic filler, 80 to 100 parts of the polymer material and 50 to 100 parts of the adhesive material in parts by mass; Preferably, the oily coating further comprises an ion conductive material; Preferably, the particle size of the ion conductive material is 600nm to 1100nm; Preferably, the ionic conductivity of the ion conductive material is 1×10 -4 S / cm~1×10 -2 S / cm; Preferably, the oily coating comprises 0.8 to 1.2 parts of the ion conductive material by mass.

4. The composite diaphragm according to claim 1 or 2, characterized in that: The composite membrane further comprises a water-based coating disposed on the other side of the base membrane away from the oily coating; Preferably, the water-based coating comprises inorganic particles, a glue layer material, a binder, a dispersant and a wetting agent; Preferably, the particle size of the inorganic particles is 100nm to 1200nm; Preferably, the adhesive layer material includes polyolefin material and / or hydrogenated nitrile rubber; Preferably, the polyolefin material includes at least one of polyethylene microspheres, polypropylene microspheres or polybutylene microspheres; Preferably, the glass transition temperature of the adhesive layer material is -20°C to 70°C; Preferably, the particle size D of the glue layer material is 10 Particle size D is ≥1.3μm, 2.8μm≤ 50 ≤7.1μm, particle size D 90 ≤11.2μm, particle size D 99 ≤13μm; Preferably, the thickness of the water-based coating is denoted as H2, and H2 is 1 μm to 3 μm; Preferably, the particle size D of the glue layer material is 50 The relationship between the thickness H2 of the water-based coating is: 0.8≤D 50 / H2≤4.2; Preferably, the aqueous coating comprises, by mass, 78 to 92 parts of inorganic particles, 3 to 16 parts of adhesive layer materials, 2.7 to 6 parts of binder, 0.25 to 1 part of wetting agent and 0.1 to 0.5 part of dispersant.

5. A method for preparing the composite diaphragm according to any one of claims 1 to 4, characterized in that: The preparation method comprises: An oily coating slurry is prepared and oily coating is performed on one surface of the base film to form an oily coating to obtain the composite diaphragm.

6. The method for preparing the composite diaphragm according to claim 5, characterized in that: The oily coating slurry includes an organic solvent, and the organic solvent includes at least one of N,N-dimethylacetamide, N-methylpyrrolidone, N,N-dimethylformamide or dimethyl sulfoxide; Preferably, the oily coating slurry further comprises a co-solvent, and the co-solvent comprises at least one of calcium chloride, lithium chloride or potassium chloride; Preferably, the mass of the co-solvent accounts for 3.5% to 6% of the total mass of the oily coating slurry; Preferably, the solid content of the oily coating slurry is 2% to 8% and the viscosity is 30cps to 60cps; Preferably, the oily coating process includes in sequence: unwinding the base film, coating with the oily coating slurry, over-solidification molding, washing and drying.

7. The method for preparing a composite diaphragm according to claim 5 or 6, characterized in that: The preparation method further comprises: preparing a water-based coating slurry, and after forming the oily coating, directly applying a water-based coating on the other side of the base film away from the oily coating without winding it up to form a water-based coating, thereby obtaining the composite diaphragm; Preferably, the aqueous coating slurry comprises an aqueous solvent, and the aqueous solvent comprises water; Preferably, the solid content of the aqueous coating slurry is 27% to 33% and the viscosity is 10cps to 80cps; Preferably, the coating surface density of the adhesive layer material in the water-based coating is 0.08 g / m 2 ~0.56g / m 2 .

8. A method for manufacturing a battery, characterized in that: The manufacturing method comprises: Providing a composite diaphragm according to any one of claims 1 to 4 or a composite diaphragm obtained by the preparation method according to any one of claims 5 to 7, and providing a positive electrode sheet, a negative electrode sheet and an electrolyte; assembling the positive electrode sheet, the negative electrode sheet and the composite diaphragm into a shape, wherein the oily coating of the composite diaphragm faces and contacts the positive electrode sheet, to obtain an electrode group; The electrode group is firstly hot-pressed to transfer the oily coating on the composite diaphragm to the positive electrode sheet, and then packaged, baked and injected with liquid in sequence to obtain the battery.

9. The method for manufacturing a battery according to claim 8, characterized in that: The assembly forming process includes a lamination process or a winding process; Preferably, the hot pressing temperature is 60°C to 90°C, the surface pressure is 0.5MPa to 3MPa, and the time is 25s to 240s; Preferably, the baking temperature is 95°C to 105°C, and the baking time is 8h to 12h; Preferably, the manufacturing method further comprises post-processing the obtained battery, wherein the post-processing comprises sequentially performing pre-charging, formation and capacity division; Preferably, the battery comprises a square-shell battery; Preferably, the positive electrode active material of the positive electrode plate includes at least one of lithium cobalt oxide, lithium manganese oxide, ternary materials, lithium iron phosphate, lithium iron manganese phosphate or lithium-rich manganese-based materials, preferably at least lithium iron phosphate.

10. A battery, characterized in that: The battery is obtained according to the manufacturing method of claim 8 or 9.

Citation Information

Patent Citations

  • Functional coating diaphragm and battery containing same

    CN106058126A

  • Oily ceramic slurry, preparation method thereof, positive plate coated with slurry and lithium ion battery

    CN112397716A

  • Composite diaphragm comprising PVDF coating with lamellar structure and preparation method thereof, and application of composite diaphragm comprising PVDF coating with lamellar structure

    CN110137414A

  • Lithium battery composite diaphragm as well as preparation method and application thereof

    CN114335904A

  • Lithium battery composite diaphragm as well as preparation method and application thereof

    CN116144071A

Cited By

  • Lithium battery coating diaphragm, preparation method thereof and lithium battery

    CN120413979A